2022
DOI: 10.4251/wjgo.v14.i4.748
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory RNAs, microRNA, long-non coding RNA and circular RNA roles in colorectal cancer stem cells

Abstract: The properties of cancer stem cells (CSCs), such as self-renewal, drug resistance, and metastasis, have been indicated to be responsible for the poor prognosis of patients with colon cancers. The epigenetic regulatory network plays a crucial role in CSC properties. Regulatory non-coding RNA (ncRNA), including microRNAs, long noncoding RNAs, and circular RNAs, have an important influence on cell physiopathology. They modulate cells by regulating gene expression in different ways. This review discusses the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 116 publications
0
13
0
Order By: Relevance
“…LncRNAs are involved in multiple physiological and pathological processes, the underlying mechanisms remain largely unknown [28][29][30]. In this study, data showed that ELFN1-AS1 was signi cantly upregulated in CRC tissues and promoted immune escape of CRC cells from NK cells.…”
Section: Discussionmentioning
confidence: 83%
“…LncRNAs are involved in multiple physiological and pathological processes, the underlying mechanisms remain largely unknown [28][29][30]. In this study, data showed that ELFN1-AS1 was signi cantly upregulated in CRC tissues and promoted immune escape of CRC cells from NK cells.…”
Section: Discussionmentioning
confidence: 83%
“…LncRNAs control cancer development and progression by attenuating gene expression through various mechanisms [24]. The actions of lncRNAs are primarily decided on the basis of their location.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SMAD2, SMAD4, and TGF-βRII genes are markedly associated with miRNA-155 and miR-22, both of which strongly correlate with tumor properties, suggesting clinical utility in immunotherapy[ 24 ]. miR-4666-3p and miR-329 act as tumor suppressor genes, affecting TGF-βR1 and thus preventing the activation of the TGF-β1/Smad pathway[ 80 ]. Finally, miR-147 overexpression has been shown to inhibit EMT and the TGF-β/SMAD pathway in colon cancer cells[ 81 ].…”
Section: Mirnas As Regulators In Crcmentioning
confidence: 99%